2021
DOI: 10.5045/br.2021.2021107
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a comorbidity index for predicting survival outcomes after allogeneic stem cell transplantation in adult patients with acute leukemia: a Korean nationwide cohort study

Abstract: Development and validation of a comorbidity index for predicting survival outcomes after allogeneic stem cell transplantation in adult patients with acute leukemia: a Korean nationwide cohort study. Blood Res 2021.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…It carries a comprehensive set of databases comprising the health information of 50 million Koreans, including demographic variables such as age and sex, and medical treatment databases harboring universal medical claims and mortality data involving the whole Korean population 15 . Accordingly, KNHIS database has contributed to various epidemiological investigations into hematologic disease 16‐20 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It carries a comprehensive set of databases comprising the health information of 50 million Koreans, including demographic variables such as age and sex, and medical treatment databases harboring universal medical claims and mortality data involving the whole Korean population 15 . Accordingly, KNHIS database has contributed to various epidemiological investigations into hematologic disease 16‐20 …”
Section: Methodsmentioning
confidence: 99%
“…15 Accordingly, KNHIS database has contributed to various epidemiological investigations into hematologic disease. [16][17][18][19][20] The study protocol is described in Figure 1. For patients in the primitive case and case cohorts, the index date was defined as the date of allo-SCT, whereas the index date was indicated as the year of participation in the public health checkup for individuals in the primitive control and control cohorts.…”
Section: Data Sourcementioning
confidence: 99%
“…Because the AML is primarily a disease of the elderly with a median age at diagnosis over 60 years 4,5 , the use of reduced intensity conditioning (RIC) regimens has broadened the applicability of allogeneic HSCT to older adults with AML 6,7 . Historically, RIC was recognized as an 'unavoidable' alternative to myeloablative conditioning (MAC) for administering HSCT to fragile patients with an increasing concern of higher risk of relapse at the cost of lower treatment-related mortality 6,8,9 . Recently, however, similar outcomes between MAC and RIC in terms of post-HSCT survival and relapse in patients with AML were reported in a series of prospective studies [10][11][12] and RIC was suggested a reasonable option even in a subset of young and healthy patients.…”
Section: Introductionmentioning
confidence: 99%